NUTRITIONAL STRATEGIES AND INNOVATIVE TECHNOLOGIES FOR MAINTAINING THE OPERATIONAL READINESS OF MILITARY PERSONNEL IN EXTREME CONDITIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Executing special missions in extreme conditions requires military personnel to maintain optimal physical and mental performance. This necessitates meticulous planning of rations and beverages to provide sufficient energy, hydration, and immune system support. To enhance interoperability among NATO member states, STANAG 2937 was introduced, standardizing the minimum characteristics and quality assurance of individual operational rations for military use. Key requirements defined in STANAG 2937 include nutritional adequacy, stability, durability, and tailored rations for specific conditions. Rations must provide 4000–6000 calories per day in extreme environments, prioritizing carbohydrates for quick energy, followed by fats and proteins. Packaging must ensure durability, ease of transport, and content preservation. Nutritional supplements, such as energy bars, vitamins, and isotonic drinks, are vital for sustaining energy and overall health. Extreme temperatures significantly influence macronutrient needs. In cold climates, higher fat intake (35–40%) supports energy reserves, while proteins preserve muscle mass and aid thermoregulation. Conversely, in hot climates, increased carbohydrate consumption (55–65%) replenishes glycogen and mitigates energy loss. Vitamins and minerals, such as B-complex, vitamin C, and magnesium, are essential for metabolic functions, immune health, and physical endurance.